2014
DOI: 10.1097/brs.0000000000000472
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Vertebral Body Tethering for Idiopathic Scoliosis

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(156 citation statements)
references
References 29 publications
6
132
2
7
Order By: Relevance
“…8 Ultimately, research based on the staple led to further advances, and current investigations into a vertebral body tether are ongoing. 48 Currently, the most commonly adopted surgical approach is posterior spinal fusion with or without multiple Ponte osteotomies with derotation techniques to provide correction. Pedicle screw instrumentation is used to sta-bilize the correction, and arthrodesis is augmented with biologics per surgeon preference.…”
Section: 64mentioning
confidence: 99%
“…8 Ultimately, research based on the staple led to further advances, and current investigations into a vertebral body tether are ongoing. 48 Currently, the most commonly adopted surgical approach is posterior spinal fusion with or without multiple Ponte osteotomies with derotation techniques to provide correction. Pedicle screw instrumentation is used to sta-bilize the correction, and arthrodesis is augmented with biologics per surgeon preference.…”
Section: 64mentioning
confidence: 99%
“…[5] and Samdani et al [6] reported growth-modulating convex vertebral body stapling and/or convex vertebral body tethering as a nonfusion surgical alternative for idiopathic scoliosis that occurs before the onset of the adolescent growth spurt. The published clinical results of that technique are promising [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…The published clinical results of that technique are promising [4][5][6]. The indications chosen for the use of ApiFix® in managing moderate AIS are almost identical to the indications of vertebral body tethering, although the surgical approach (posterior vs. anterior) and the age of the patients are different [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are not intended for EOS patients. Shape memory alloy staples and flexible anterior spinal tethers have been tested clinically with promising results [81,82], but none of the devices for spinal growth modulation have been approved for human use by the FDA and thus are still investigational.…”
Section: Compression Based Implantsmentioning
confidence: 99%